SAMHD1 Mutations and Expression in Mantle Cell Lymphoma Patients - Wang, Tao; Yue, Wenqin; Tang, Gusheng; Ye, Mingyu; Yu, Jiechen; Liu, Bin; Jiao, Lijuan; Liu, Xuefei; Yin, Shuyi; Chen, Jie; Gao, Lei; Yang, Jianmin; et al. (Frontiers in Oncology, 2021)
SAMHD1 (Sterile alpha motif domain and histidine-aspartate domain-containing protein 1) is a deoxynucleoside triphosphate triphosphohydrolase regulating innate immune and modulating DNA damage signaling. It plays an important role in the development of some tumors. SAMHD1 was also reported as a barrier to cytarabine, a common chemotherapy drug for mantle cell lymphoma (MCL), and as a biomarker of grim prognosis for acute myelocytic leukemia (AML) patients. However, SAMHD1 expression and function in MCL has not been well-defined. In the present study, we evaluated SAMHD1 expression by immunohistochemistry and its gene structure by Sanger sequencing in MCL. Our results showed that SAMHD1 was positive in 36 (62.1%) patients. Importantly, SAMHD1 positive patients was associated with lower chemotherapy response rate (p=0.023) and shorter overall survival (p=0.039) than SAMHD1 negative cases. These results suggest that SAMHD1 is an adverse biomarker for MCL patients, which is due to the high expression of SAMHD1 and rapid cell proliferation. These findings were confirmed in in vitro study using siRNA technique. Silencing SAMHD1 gene in MCL cell line Jeko-1 significantly decreased cell proliferation and increased cell apoptosis. MCL cell line with SAMHD1 knock-down showed lower ki-67 proliferation index, higher Caspase-3, and more sensitive to cytarabine. Furthermore, for the first time, four previously unreported missense mutations (S302Y, Y432C, E449G and R451H) in exon 8 and exon 12 of SAMHD1 gene were discovered by sequencing. The mutations had not been found to corelate with SAMHD1 protein expression detected by Immunohistochemistry. The biological functions of this mutated SAMHD1 remain to be investigated.